Characterization of multidrug-resistant genes of Klebsiella pneumoniae from clinical isolates in Asaba, Delta State, Nigeria - Johnson Udo; Pius Omosigho; Olalekan Okesanya (Microbes and Infectious Diseases, 2025)
Background: The awakening of multidrug-resistant (MDR) Klebsiella pneumoniae strains is a major public health issue. Thus, this study aims to characterize MDR genes of K. pneumoniae isolates from clinical samples. Methods: This is a descriptive cross-sectional study conducted at the Federal Medical Centre, Asaba. Cultural and biomedical methods were employed in identifying K. pneumoniae. Modified Kirby-Bauer disc diffusion method was used for the antibiotic susceptibility. The double-disc synergy test revealed ESBL production, Imipenem disc phenotypically assessed carbapenemase production using a modified Hodge test, and multiplex PCR was used to identify resistant genes. Results: Out of 365 specimens, 51 (13.97%) isolates were positive for Klebsiella species and 21 (41.18%) K. pneumoniae, having been identified using API 20E. The resistant patterns of K. pneumoniae isolates were amoxicillin 100%, Augmentin 38.1%, Gentamicin 38.1%, Ciprofloxacin 38.1%, Nitrofurantoin 100%, Cefotaxime 100%, Ceftazidime 52.3%, Ceftriaxone 38.1%, Cefpodoxime 100%, Cefuroxime 38.1%, Ofloxacin 48.0%, Tetracycline 52.3%, Imipenem 4.80%, Levofloxacin 33.3%, and Meropenem 100%, respectively. 90% of K. pneumoniae samples had ESBL-producing properties. The genotypical ESBL genes detected were SHV 61.9% (13) CTX-M 76.2% (16), and QnrB 23.8% (5), while mixed genes of SHV and CTX-M 52.4% (11), SHV, CTX-M and QNRB  19.1% (4). Carbapenem-producing K. pneumoniae was detected in 4.76% (1) phenotypically, and genotypically, KPC was identified. Conclusion:: The study emphasizes the widespread nature of MDR K. pneumoniae strains in clinical settings.